Characteristics of patients with drug resistant and drug sensitive tuberculosis in East London between 1984 and 1992. Issue 8 (August 1994) - al Jarad, N; Parastatides, S; Paul, E A; Sheldon, C D; Gaya, H; Rudd, R M; Empey, D W
Abstract : BACKGROUND–The aim of this study was to investigate retrospectively factors associated with drug resistant tuberculosis at the London Chest Hospital. METHODS–The microbiology results for patients with tuberculosis at the hospital for the period 1984-92 were reviewed, together with case notes and chest radiographs of all patients with drug resistant tuberculosis and of 101 patients with drug sensitive tuberculosis notified during the same period as a control group. RESULTS–Culture positive pulmonary tuberculosis occurred in 292 patients. Drug resistant strains were isolated from 20 patients (6.8%). Ten of the 292 (3.4%) had strains resistant to a single drug and nine (3.1%) had resistance to more than one first line drug. One patient had strains resistant to isoniazid and capreomycin. Strains resistant to more than one drug were all resistant to isoniazid and rifampicin. In five patients these strains were also resistant to pyrazinamide and in two they were resistant to streptomycin. Single drug resistant strains were resistant to isoniazid (nine patients) or streptomycin (one patient). Among the risk factors studied previous treatment for tuberculosis was the most significant association with drug resistant tuberculosis (7/9) for patients with resistance to more than one drug; 5/11 for single drug resistance compared with 6/101 patients in the drug sensitive group (odds ratio 22.8). Other risk factors were bilateral disease at presentation (odds ratio 8.5), and disease at a young age (odds ratio 1.03). CONCLUSIONS–Previous treatment for tuberculosis and bilateral disease at presentation were found to be more commonly associated with cases of drug resistant than with drug sensitive tuberculosis.